Thermal Characterization, Compositional Analysis and Extraction of Elemental Powder from Rohu Fish Residue used as Composite Particulate - Bansal, Gagan; Jain, Animesh; Singh, V. K.; Gope, P. C. (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*319.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927659);" role="presentation">The efforts were made for the laboratory preparation of useful elemental based powder from the waste/residue <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*333.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.960129);" role="presentation">of Rohu fish. The concept was initially applied similar to the process of extracting silica from ash. Extracted <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*346.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.917608);" role="presentation">Residue Powder (ERP) thus obtained <span dir="ltr" style="left: calc(var(–scale-factor)*227.57px); top: calc(var(–scale-factor)*346.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925018);" role="presentation">by systematic processing of fish residue contained many noble elements <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*359.57px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948016);" role="presentation">like Silica, Calcium, Carbon, Magnesium, Sodium etc. which were scrutinized later by FESEM compositional <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*372.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00051);" role="presentation">analysis. The ERP was used as a particulate in the epoxy based composite where i<span dir="ltr" style="left: calc(var(–scale-factor)*439.18px); top: calc(var(–scale-factor)*372.77px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958554);" role="presentation">t shows appreciable <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*385.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.916556);" role="presentation">compatibility, bonding characteristics and enhancement in mechanical properties. The extracted residue powder <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*399.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954377);" role="presentation">resulted in good thermal and decomposition characteristics as seen in TGA analysis at <span dir="ltr" style="left: calc(var(–scale-factor)*440.26px); top: calc(var(–scale-factor)*399.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933911);" role="presentation">320 and 720 degree <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*412.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894157);" role="presentation">centigrade.